Genomic analysis of methicillin-resistant Staphylococcus aureus clonal complex 239 isolated from Danish patients with and without an international travel history - Coppens, Jasmine; Xavier, Basil Britto; Vlaeminck, Jelle; Larsen, Jesper; Lammens, Christine; Van Puyvelde, Sandra; Goossens, Herman; Larsen, Anders Rhod; Malhotra-Kumar, Surbhi (Frontiers in Microbiology, 2022)
Introduction International travel has been a major determinant for the introduction of pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) into naïve geographic areas. MRSA clonal complex 239 (CC239) is a highly virulent clone that is predominant in Asia. The objective of this study was to determine the geographic origin of MRSA CC239 isolates recovered from Danish cases with or without a history of international travel during 2004–2016. Materials and methods Human MRSA isolates with spa types t030 and t037 (n = 60) were obtained from the National Reference Laboratory for Antimicrobial Resistance. For each case, the following data were collected from notification forms: sex, age, isolation year, specimen source (screening swab or clinical sample), infection type, and international travel history. All isolates were whole-genome sequenced, and a comparative genome and phylogenetic analysis was performed. Results The majority of isolates originated from skin and soft tissue (SST) infections and screening swabs. In 31 out of 60 cases reported international travel to different parts of the world. Fifty-four isolates belonged to CC239, including sequence type 239 (ST239) (n = 43), ST241 (n = 5), ST4377 (n = 2), ST4378 (n = 1), ST1465 (n = 1), ST343 (n = 1), and ST592 (n = 1). The majority of the CC239 MRSA isolates (40/54) belonged to well-known geographic clades, including the Asian (n = 12), Serbian (n = 11), South American (n = 2), and Turkish (n = 15). Most MRSA ST239 isolates belonging to the highly virulent Asian clade carried sasX and were recovered from individuals who had travelled to Asia, Africa and the Middle East. Conclusion Our data reveal multiple introductions of MRSA CC239 into Denmark through international travel, which highlights the importance of continued genomic surveillance of MRSA in persons returning from international travel to areas where MRSA is endemic.